Pelatihan penggunaan podcast dan audiobook untuk meningkatkan kemampuan berbicara peserta kursus di LKP-MEC Namlea - Rahman, Abd; Azwan, Azwan (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2022)
Speaking skills are vital skills for the LKP MEC course participants to meet their needs in facing the world of the job.  The training on using podcasts and audiobooks to improve speaking skills took place for eight meetings. In the training process, the participants were first guided on the procedures for accessing and using podcasts or audiobooks through projector media to provide knowledge about information and communication technology to improve speaking skills. Furthermore, podcasts and audiobooks can also be accessed through each trainee's device/mobile phone so that they can listen to English conversations independently. Conversational materials on podcasts and audiobooks included in authentic materials that help participants gain knowledge of the language. To hone speaking skills in the training process, each participant imitates the speaker's way of speaking, accent, dialect, and pronunciation. In addition, they record vocabulary and sentences and practice speaking in pairs using each language knowledge they acquire consistently. As many as 15 people or 75 per cent of the participants who had attended the training were declared competent in mastering speaking skills and fluency in having dialogue using a variety of spoken English properly and correctly until they were finally accepted for an internship at the Grand Sarah Hotel of Namlea.